Persepsi mahasiswa terhadap Pusat Kaunseling dan Kerjaya, Universiti Teknologi Malaysia, Skudai, Johor - Mohd. Sahid, Mohd. Fami (2009)
The research aims to show students perceptions about Counselling and Career Centre services in Universiti Teknologi Malaysia (UTM), Skudai. The research method was survey by using questionnaire to collect the data from the respondents. A random respondents of 150 students were selected. A set of questionnaire containing 36 items divided into 4 parts. Part A : Respondent’s background. Part B : Student’s perceptions about knowledge on Counseling and Career Centre. Part C : Student’s perceptions about Counselling and Career Centre services. Part D : Student’s perceptions about Psycology Officers in Counselling and Career Centre. A set of questionnaire was distributed to the respondents and were analyzed descriptively to obtain the frequency, percentage and mean for each item using Statistical Package for Social Science (SPSS) 12.0 for Windows. It was found that the repondents agreed with the guidance and counselling services in Counselling and Career Centre. The total mean was 3.74. The result of the research showed that the respondents agreed about the knowledge on Counselling and Career Centre with the total mean of 3.72. The respondents also agreed about the services by the Counselling and Career Centre with the total mean of 3.79. The respondents agreed with the services given by Psychology Officers with the total mean was 3.71. As a conclusion the guidance and counseling services was important to the students of UTM. Therefore, in order to provide the services for students, variety of suggestions were given to improving the quality of services in Counselling and Career Centre towards realized the mission and vision of UTM.